Philosophy of Education: Islamic Educational Thought of Ibn Sina - Ariesta Setyawati (Equilibrium: Jurnal Pendidikan, 2024)
Education is guidance, leadership, from educators to students with physical and spiritual development, education systematically shapes the character, nature and behavior of students. In the world of education there are several educational figures who explore the world of education, one of which is Ibn Sina. Ibn Sina (Avicenna) was a well-known Muslim philosopher in the field of medicine, but many of his ideas were also related to education and are considered to have contributed to the development of modern educational thought. The purpose of this study is to analyze Ibn Sina's educational thinking and his contribution to Islamic education in modern times. In this writing using descriptive and qualitative methods with literature studies and data sources obtained from research whose subjects are in the form of literature and raised from documentation derived from scientific journals, e-books, and other related reference sources.